2020
DOI: 10.7554/elife.61773
|View full text |Cite
|
Sign up to set email alerts
|

chTOG is a conserved mitotic error correction factor

Abstract: Accurate chromosome segregation requires kinetochores on duplicated chromatids to biorient by attaching to dynamic microtubules from opposite spindle poles, which exerts forces to bring kinetochores under tension. However, kinetochores initially bind to microtubules indiscriminately, resulting in errors that must be corrected. While the Aurora B protein kinase destabilizes low-tension attachments by phosphorylating kinetochores, low-tension attachments are intrinsically less stable than those under higher tens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 78 publications
6
41
3
Order By: Relevance
“…Our analysis of attachment status showed that chTOG1, EB1-EB3 complex and SKA complex are not essential for maintaining end-on attachments in the absence of Aurora-B activity (Supplementary Table 1 and Supplementary Fig. 1d ), consistent with intact kinetochore-microtubule attachment in cells depleted of chTOG1 50 , 51 , EB1 47 , APC 47 or SKA3 44 , 52 in the absence of microtubule-destabilising cold treatment. Uniquely Astrin or SKAP depleted cells showed a reduction in the number of end-on attached kinetochores and loss of bouquet-like chromosome arrangement in monopolar spindles in this screen (Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…Our analysis of attachment status showed that chTOG1, EB1-EB3 complex and SKA complex are not essential for maintaining end-on attachments in the absence of Aurora-B activity (Supplementary Table 1 and Supplementary Fig. 1d ), consistent with intact kinetochore-microtubule attachment in cells depleted of chTOG1 50 , 51 , EB1 47 , APC 47 or SKA3 44 , 52 in the absence of microtubule-destabilising cold treatment. Uniquely Astrin or SKAP depleted cells showed a reduction in the number of end-on attached kinetochores and loss of bouquet-like chromosome arrangement in monopolar spindles in this screen (Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…1 C; ), consistent with previous observations ( Gergely et al, 2000 , 2003 ; Royle et al, 2005 ; Foraker et al, 2012 ; Bendre et al, 2016 ; Herman et al, 2020 ). Overexpression of TACC3 can result in the formation of aggregates ( Gergely et al, 2000 ; Hood et al, 2013 ), which have recently been described as liquid-like phase-separated structures ( So et al, 2019 ).…”
Section: Resultssupporting
confidence: 92%
“…A further component of the response to erroneous attachment is the plus-end microtubule polymerase, Stu2 (the yeast ortholog of XMAP215/ch-TOG in metazoans). Its polymerization activity depends on plus-end binding, through a set of N-terminal TOG domains ( Figure 1A ; Al-Bassam et al, 2006 ; Ayaz et al, 2012 ; Ayaz et al, 2014 ; Fox et al, 2014 ), but its kinetochore association is independent of microtubules ( Hsu and Toda, 2011 ; Kakui et al, 2013 ; Miller et al, 2016 ; Miller et al, 2019 ; Vasileva et al, 2017 ; Herman et al, 2020 ). In single-molecule experiments in vitro, kinetochores under low tension detach more frequently from microtubules than under higher tension ( Akiyoshi et al, 2010 ), but only when Stu2 is present ( Miller et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%